P466 Tofacitinib for the treatment of ulcerative colitis: Up to 5.4 years of safety data from global clinical trials. (25th January 2019) - Sandborn, W J; Panés, J; Panaccione, R; D'Haens, G R; Sands, B E; Su, C; Moscariello, M; Jones, T V; Pedersen, R D; Friedman, G S; Lawendy, N; Chan, G
Abstract: Background: Tofacitinib is an oral, small-molecule Janus kinase inhibitor approved in several countries for the treatment of ulcerative colitis (UC). The efficacy and safety of tofacitinib as UC induction and maintenance therapy were evaluated in Phase (P) 2 1 and P3 2 randomised, placebo-controlled studies, and in an ongoing, open-label, long-term extension (OLE) study. 3 We report updated tofacitinib safety analyses from the UC programme, with exposure up to 5.4 years. Methods: Patients who received placebo, tofacitinib 5 or 10 mg twice daily (BID) were analysed as two cohorts: Maintenance (P3 maintenance, n = 592) and Overall (patients receiving tofacitinib 5 or 10 mg BID in P2, P3 or the OLE study, n = 1157; 2050.5 patient-years' exposure; data at November 2017). Proportions and incidence rates (IR; unique patients with events per 100 patient-years) were evaluated for adverse events (AEs) of special interest. Opportunistic infections, malignancies, major adverse cardiovascular events (MACE) and gastrointestinal perforations were reviewed by independent adjudication committees. Results in the overall Ccohort based on the previous December 2016 data cut are presented for context. Results: In total, 1157 patients received ≥1 dose of tofacitinib 5 or 10 mg BID. Demographics and disease characteristics were generally similar among treatment groups across cohorts. For the Overall Cohort, most patients ( n = 956, 83%) received an average tofacitinib dose of 10 mg BID. IR for AEs of special interest were: death, 0.2; serious infection, 1.9; herpes zoster, 3.8; opportunistic infection, 1.2; malignancy (excluding non-melanoma skin cancer [NMSC]), 0.6; NMSC, 0.8; MACE, 0.3; and gastrointestinal perforation, 0.1. Conclusions: The safety profile of tofacitinib in patients with UC was manageable, and similar to the tofacitinib rheumatoid arthritis programme and that of other UC therapies including biologics. IR for AEs of special interest did not increase with longer exposure relative to previously reported analyses from the OCTAVE programme. A dose-dependent risk of herpes zoster was observed. Reference 1. Sandborn WJ, Ghosh S, Panes J et al . Tofacitinib, an oral janus kinase inhibitor, in active ulcerative colitis. N Engl J Med 2012;367:616-24. doi:10.1056/NEJMoa1112168 2. Sandborn WJ, Su C, Sands BE. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2017;376:1723–36. doi:10.1056/NEJMoa1606910 3. Lichtenstein GR, Loftus Jr EV, Bloom S. Tofacitinib, an oral Janus kinase inhibitor, in the treatment of ulcerative colitis: open-label, long-term extension study . Am J Gastroenterol . 2017;112(S1). Abstract 714,